Rights and remedies of employees pertaining to injuries suffered during the course of employement : an analysis of the laws - Rooshida Merican Abdul Rahim Merican (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2007)
The thesis examines the relevant provisions governing the rights and remedies of employees relating to injuries suffered during the course of their employment. It is apparent that accidents that are work related will happen from time to time and this will entitle the injured employee to the rights and remedies available. The present laws in Malaysia are adequate in providing protection to the employees but some reviewing, revising and enforcement in the applicability of the regulations need to be done. Currently, it is obvious that the accident rate is distressing and inadequate, and therefore, there is an urgent need for the present provisions to be reviewed and revised. The study adopts an analysis of the statutory provisions governing the rights and remedies of employees pertaining to injuries suffered during the course of their employment and aims at identifying the strengths and weaknesses of the present law. Apart from that, the role of Social Security Organisation (SOCSO) in dealing with awarding compensations and benefits to the injured employee, and compensations under the Workmen's Compensation Act 1952 were perused. This in-depth study of the law has revealed certain shortcomings in applying the law into practice. Decided cases have proven to be significant in demonstrating the practical application of the legal provisions. A comparative study with other jurisdictions has significantly contributed to this research. In the case of Islamic law, only some specific discussions in identifying the basic law governing the problems have been made. The study has found some weaknesses of the existing provisions and the scope for further developments and improvements of the present laws with severe punishment being carried out. Accidents need to be avoided and once the workplace is safe, less accident and less injury will happen. At the same time, SOCSO should continue to provide better quality and friendlier services in order to develop Malaysia as a caring society. Therefore, the study suggests the existing provisions to be reviewed and revised periodically. One suggestion is that all accident victims should be given maximum benefits and full compensations in the shortest time possible.